Classification of Foreign Direct Investments by Theories and the Economic Growth. Case: Balkan Countries - Lazaj, Armira (Acta Universitatis Danubius. Œconomica, 2023)
The purpose of this paper is to analyze the factors that will influence the economic growth. Factors that have impeded investment and economic development in these nations include political unrest, weak institutions, and restricted access to credit and finance. (OECD 2021). The region’s current socio-economic conditions provide an impetus for Balkancountries governments to induce more foreign investment as a mechanism for fostering economic growth FDI promotes economic growth in both the host country and the country of origin. The host country benefits from FDI by financing projects planned, developing new technologies and generating new jobs. Investing companies benefit from the expansion of markets and, consequently, the growth of their shares in international markets. The world is full of development opportunities, be it for countries that have just begun to modernise to the richest countries. Overall, the region's economic growth and development still have a lot of room for improvement, even though some Balkan nations have made strides in recent years. Higher rates of economic growth and development in the Balkans may be facilitated by policies aimed at enhancing political stability, bolstering institutions, decreasing corruption, encouraging investment, and expanding access to finance.